2011
DOI: 10.21608/ejana.2011.3663
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chronic Aspartame Administration on the Kidney of Albino Rat

Abstract: Background: Aspartame is a widely employed synthetic sweetener used in diet control and by diabetic patients. Its safety based on the findings of the previous studies showed controversy. Aim of the Work: The aim of this study was to demonstrate the chronic effect of aspartame on the structure of the kidney in the newborn, adult and old albino rats. Materials and Methods: In this work, 60 albino rats were used, 40 of which were three month old, while the remaining 20 rats were twelve month old at the beginning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Furthermore, histological findings by Gabr et al revealed glomerular and renal tubular damage in rats treated with 20 mg/kg/day aspartame for 180 days [ 14 ]. The current study tested aspartame administration for eight weeks; thus, the effects of long-term aspartame administration cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, histological findings by Gabr et al revealed glomerular and renal tubular damage in rats treated with 20 mg/kg/day aspartame for 180 days [ 14 ]. The current study tested aspartame administration for eight weeks; thus, the effects of long-term aspartame administration cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed harmful effects on several organs such as the liver and kidneys. 3,25,26 The current research was undertaken to investigate the ameliorative effect of white honey on harmful changes caused by high dose of multivitamins in the liver tissue of albino rats. The impact of multivitamins was evident on the hepatic tissue, where tissue degradation and amendment in structure of liver cells showed signs of cellular death (necrosis).…”
Section: Effects Of Multivitamins and White Honey On Histological Strmentioning
confidence: 99%